Incidence of a single subsegmental mismatched perfusion defect in single-photon emission computed tomography and planar ventilation/perfusion scans. Issue 2 (February 2017) - Stubbs, Matthew; Chan, Kenneth; McMeekin, Helena; Navalkissoor, Shaunak; Wagner, Thomas
Abstract : Objective: This study aims to compare the incidence of ventilation/perfusion (V/Q) scans interpreted as indeterminate for the diagnosis of pulmonary embolism (PE) using single-photon emission computed tomography (SPECT) versus planar scintigraphy and to consider the effect of variable interpretation of single subsegmental V/Q mismatch (SSM). Methods: A total of 1300 consecutive V/Q scans were retrospectively reviewed. After exclusion and matching for age and sex, 542 SPECT and 589 planar scans were included in the analysis. European Association of Nuclear Medicine guidelines were used to interpret the V/Q scans, initially interpreting SSM as negative scans. Patients with SSM were followed up for 3 months and further imaging for PE was collected. Results: Indeterminate scans were significantly fewer in the SPECT than the planar group on the basis of the initial report (7.7 vs. 12.2%, P <0.05). This is irrespective of classification of SSM as a negative scan (4.6 vs. 12.1%, P <0.0001) or an indeterminate scan (8.3 vs. 12.2%, P <0.05). Of the 21 patients who had SSM, 19 underwent computer tomography pulmonary angiogram and embolism was found in one patient. None of these patients died at the 3-month follow-up. Conclusion: V/Q SPECT has greater diagnostic certainty of PE, with a 41% reduction in an indeterminate scan compared with planar scintigraphy. This is irrespective of the clinician's interpretation of SSM as negative or intermediate probability. Patients with SSM would not require further computer tomography pulmonary angiogram imaging.